2021
DOI: 10.1097/mlr.0000000000001678
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Postoperative Readmission Rates Between Veterans Receiving Total Knee Arthroplasty in the Veterans Health Administration Versus Community Care

Abstract: Background: There are growing concerns that Veterans' increased use of Veterans Health Administration (VA)-purchased care in the community may lead to lower quality of care.Objective: We compared rates of hospital readmissions following elective total knee arthroplasties (TKAs) that were either performed in VA or purchased by VA through community care (CC) at both the national and facility levels.Methods: Three-year cohort study using VA and CC administrative data from the VA's Corporate Data Warehouse (Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Other studies compared VA and community care purchased by the VA and focused on select subpopulations having a particular condition or receiving a particular procedure. 17 , 18 , 19 , 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…Other studies compared VA and community care purchased by the VA and focused on select subpopulations having a particular condition or receiving a particular procedure. 17 , 18 , 19 , 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] VA-performed surgical procedures, such as total knee arthroplasties (TKAs), have comparable or lower overall rates of complications and readmissions than VA-purchased surgical procedures. [8][9][10] However, these findings may obscure quality differences across VA facilities and across community health care facilities from whom the VA purchases care.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of surgical outcomes in VA and non-VA care settings rapidly followed. [3][4][5] These studies were well powered to determine quality of care for veterans overall and showed that surgical outcomes were either equivalent or better in VA hospitals. However, these studies were 90% male.…”
mentioning
confidence: 99%
“…Veterans could now choose to have their surgical care at a VA hospital or at a community or academic hospital. Comparisons of surgical outcomes in VA and non–VA care settings rapidly followed . These studies were well powered to determine quality of care for veterans overall and showed that surgical outcomes were either equivalent or better in VA hospitals.…”
mentioning
confidence: 99%